PENGARUH KUALITAS PRODUK DAN CITRA MEREK TEHADAP MINAT BELI KONSUMEN HANDPHONE NOKIA PADA TOKO SIDOARJO UNAAHA - Melati (FEB Universitas Lakidende, 2020)
This study aims to determine and explain the effect of product quality and brand image on buying interest of Nokia Mobile consumers at Sidoarjo Unaaha Stores. The population in this study were consumers of Nokia Mobile Phones at Sidoarjo Unaaha Store, amounting to 30 people. This study uses multiple linear regression analysis. The results showed that: (1) Product quality variables significantly influence the buying interest of Nokia mobile consumers in Sidoarjo Unaaha Store. The better the quality of the products provided, the higher the buying interest of Nokia mobile consumers at Sidoarjo Unaaha Stores. (2) The brand image variable significantly influences the buying interest of Nokia mobile consumers at Sidoarjo Unaaha Stores. The better the brand image given to consumers, the higher the buying interest of Nokia mobile consumers at Sidoarjo Unaaha Store